2006
DOI: 10.1016/j.ygeno.2006.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of sex-specific and 17β-estradiol-responsive genes in the Japanese medaka, Oryzias latipes, using oligonucleotide microarrays

Abstract: Gene profiling of Japanese medaka (Oryzias latipes) was performed using an oligonucleotide DNA microarray representing 22,587 TIGR O. latipes gene indices (OLGIs). The average correlation coefficients for gene expression between individual mature fish were high (>0.95) for both female and male, indicating that the physiological status of medaka is highly reproducible under prescribed growth conditions. Of the 22,587 OLGIs, 2575 showed significant differences in expression between female and male. Exposure to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…The microarray data from fish (both sexes) exposed to 10 ng/L from the present study and available microarray data from three other exposure studies with fish and estradiol (E 2 ) or EE 2 were used in the meta-analysis [16,20,22]. Information about the different studies is shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microarray data from fish (both sexes) exposed to 10 ng/L from the present study and available microarray data from three other exposure studies with fish and estradiol (E 2 ) or EE 2 were used in the meta-analysis [16,20,22]. Information about the different studies is shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…We also identified estrogen-responses shared between fish species, experimental conditions and analytical platforms. This was achieved by a meta-analysis using our dataset together with results from three recently published articles describing hepatic gene expression profiles in fish exposed to estrogens [16,20,22]. …”
Section: Introductionmentioning
confidence: 99%
“…Sex reversal males are considered to be the consequence of the transformation from testes to ovaries during early gonadal development under the direct influence of environmental estrogens (Zha et al 2008). The sex of genetic male medaka can be functionally reversed if estrogens such as E1, E2, EE2 and EV are applied during a sensitive period of embryonic or juvenile development (Kishi et al 2006;Pettersson et al 2006;Lei et al 2013a, b). Even if a weakly estrogenic pesticide such as o,p'-DDT is present during the critical period of gonadal development, it can profoundly alter sex (Edmunds et al 2000).…”
Section: Discussion Embryonic Development and Growth Of Fishmentioning
confidence: 99%
“…This could be due to the fact that there are important changes in proteins and metabolites within cells that are not detectable by just studying the levels of mRNAs. Therefore, proteomics and metabolomics are often used to complement genomics for toxicological and health studies [16,3].…”
Section: Omics-based Vs Traditional Environmental Toxicologymentioning
confidence: 99%
“…These and other OMICS studies help to reduce uncertainties associated with the ecological and health risk assessment process by deciphering toxicity mechanisms and modes of action [7][8][9], identifying biomarkers of exposure and toxicity [10], studying toxic effects and environmental diseases [11,12], and facilitating cross-species extrapolation [13,14]. A combination of genomic, proteomic, and bioinformatic approaches was also used to study toxic mechanisms of fungicides [15], and toxicity pathways of endocrine disrupting chemicals with different known or unknown toxic modes of action [16]. These integrated OMICS studies provided novel insights into toxic mechanisms and/or modes of action of environmental chemicals.…”
Section: Introductionmentioning
confidence: 99%